Analisis Dimensi Internasional Konflik Papua dalam Model Counterinsurgency (COIN) - Muhammad Angga Ramdhan (Parahyangan Center for International Studies, 2021)
ABSTRACTMcCormick counter-insurgency diamond model is staple theoretical framework to describe Indonesia’s military strategy in quelling Papuan insurgencies. The paper offers new meaning in interpreting the model by focusing on the lens of conflict and international relations studies. To achieve its purpose, this paper use qualitative method of literature study to explain why the internationalization of unresolved Papuan issues can hinder Indonesian government efforts to win the war against Papuan insurgencies. The result shown in the analysis identified that impunity and economic inequalities had become the triggering factor for Papuan conflict internationalization, making the conflict more complex, and ended strengthening insurgency groups against Indonesian government. Thus the paper recommends to address impunity and economic inequality first before attempting to eliminate the Papuan insurgency groups.